2018
DOI: 10.1101/503102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell analysis of Crohn’s disease lesions identifies a pathogenic cellular module associated with resistance to anti-TNF therapy

Abstract: Clinical benefits to cytokine blockade in ileal Crohn's disease (iCD) have been limited to a subset of patients. Whether cellular and molecular heterogeneity contributes to variability in treatment responses has been unclear. Using single cell technologies combining scRNAseq, CyTOF and multiplex tissue imaging, we mapped the cellular landscape of inflamed ileum lesions, adjacent non-inflamed ileum and matched circulating blood cells of iCD patients.In inflamed tissues, we identified a pathogenic module charac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
226
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(233 citation statements)
references
References 97 publications
5
226
2
Order By: Relevance
“…The majority receptors for coronavirus entry were highly expressed in enterocytes in epithelial cells and mononuclear phagocytes, stromal cells and glial cells in immune cells ( Fig. 1b) [8]. In the complete view of ileum cells, we summarized here that the majority of coronavirus are likely to infect enterocytes that highly expressed specific receptors for coronavirus binding.…”
Section: The Potential Target Cells Of Coronaviruses Are Conserved Inmentioning
confidence: 83%
“…The majority receptors for coronavirus entry were highly expressed in enterocytes in epithelial cells and mononuclear phagocytes, stromal cells and glial cells in immune cells ( Fig. 1b) [8]. In the complete view of ileum cells, we summarized here that the majority of coronavirus are likely to infect enterocytes that highly expressed specific receptors for coronavirus binding.…”
Section: The Potential Target Cells Of Coronaviruses Are Conserved Inmentioning
confidence: 83%
“…This study also identified a gene signature that associates with anti-TNF and anti-integrin therapy response 123 . In CD, a recent study investigating cellular subsets in ileal CD identified a unique cellular module in inflamed tissue that includes IgG plasma cells, mononuclear phagocytes, activated T cells and stromal cells (GIMATS module) 125 . The presence of this module in patients at diagnosis was associated with a failure to achieve durable corticosteroid remission with anti-TNF therapy 125 .…”
Section: Personalising Therapies In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Next, we analyzed data set from a publicly available single-cell RNA-sequencing experiment 23 of inflamed and uninflamed ileal tissue (biopsies) obtained from CD patients. Unsupervised clustering analysis identified 22 cluster blocks ( Fig.…”
Section: Elevated Sp140 Expression In Inflammatory Diseases and Mucosmentioning
confidence: 99%